Effects of city-wide 20 mph (30km/hour) speed limits on road injuries in Bristol, UK. Issue 1 (13th July 2019) - Bornioli, Anna; Bray, Isabelle; Pilkington, Paul; Parkin, John
Abstract : Twenty miles per hour (32 km/hour) or 30 km/hour speed limits represent a potential strategy to reduce urban road injuries and are becoming increasingly widespread. However, no study has conducted a robust evaluation of the effects of city-wide 20 mph speed limits on road injuries. This study reports the effects of such an intervention, based on a natural experiment that took place in Bristol, UK. Based on a stepped-wedge design using count data, negative binomial regressions showed that between 2008 and 2016, the 20 mph speed limit intervention was associated with a city-level reduction of fatal injuries of around 63% (95% CI 2% to 86%), controlling for trends over time and areas. There was also a general trend of reduction of the total number of injuries at city level and in 20 mph roads. These findings highlight the potential benefits of city-wide 20 mph speed limits. We hypothesise that this city-wide approach may encourage a general behaviour change in drivers that, in turn, may contribute to reducing injuries across the city.